2012
DOI: 10.4103/0974-7753.100087
|View full text |Cite
|
Sign up to set email alerts
|

Acantholytic hair casts: A dermoscopic sign of pemphigus vulgaris of the scalp

Abstract: We report the dermoscopic features of pemphigus vulgaris (PV) involving the scalp of a 57-year-old African-American female. Among our findings, there were hair casts – movable tubular structures that envelop the hair shafts. We suggest that the development of those casts occurs through acantholysis within the outer root sheath, a mechanism not yet considered in the literature. This report also highlights how dermoscopy may contribute to the evaluation of disease activity, especially in those cases of PV in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…Apart from scaly well‐defined hair casts, in four patients with PV, poorly‐defined white cotton wool‐like perifollicular structures were observed. This feature was first reported by Pirmez et al . who suggested that the presence of hair casts in PV results from acantholysis in the structures of the hair shaft.…”
Section: Commentsupporting
confidence: 52%
See 1 more Smart Citation
“…Apart from scaly well‐defined hair casts, in four patients with PV, poorly‐defined white cotton wool‐like perifollicular structures were observed. This feature was first reported by Pirmez et al . who suggested that the presence of hair casts in PV results from acantholysis in the structures of the hair shaft.…”
Section: Commentsupporting
confidence: 52%
“…Literature data on trichoscopy and autoimmune bullous diseases are scarce. Our literature search revealed two papers on the usability of trichoscopy in pemphigus . There are neither literature data on the use of trichoscopy in BP nor in DH.…”
Section: Commentmentioning
confidence: 99%
“…They suggested that factors other than anti‐Dsg antibodies may be responsible for the alopecia, and proposed bacterial infection as a contributory factor. Pimez reported a patient with PV presenting with normal anagen hair loss covered by hair casts, and attributed this dermoscopic feature to acantholysis in the outer root sheath.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of pemphigus vulgaris and its trigger is unknown and it is present in the scalp, but hair loss in this disease is rarely seen and is often caused by secondary infection [4,5,9] most researchers report a secondary bacterial infection as the cause of hair folliculitis [5].…”
Section: Discussionmentioning
confidence: 99%